Neonatal Resuscitation: State of the Art - Trevisanuto, Daniele; Galderisi, Alfonso (American Journal of Perinatology, 2019)
The objective of this study is to revise novel evidence and forthcoming clinical trials that focused on the gap of knowledge raised during the 2015 guidelines for neonatal resuscitation. Literature search on main topics on neonatal resuscitation published after 2015 edition of the consensus on science and guidelines was performed. Only relevant articles (mainly randomized controlled trials [RCTs] and meta-analyses) were included and presented as descriptive review. In the past years, new RCTs and/or meta-analyses have become available on umbilical cord clamping and umbilical cord milking, oxygen concentrations to start resuscitation in term and preterm infants, use of laryngeal mask, sustained lung inflation, less invasive surfactant administration, and heart rate assessment. Despite the increasing available literature on neonatal resuscitation in the past years, many interventions are still performed without robust scientific evidence. Adequately powered and well-designed RCTs are needed to optimize management of neonates at birth.
Keywords: neonatal resuscitation; oxygen concentration; preterm infant; thermal; umbilical cord clamping; ventilation